Task Scheduling Algorithm Based on Bacterial Foraging Optimization (BFO) in Cloud Computing - Gupta, Anupama; Kaur, Kulveer; Kaur, Rajvir (Asian Journal of Engineering and Applied Technology, 2018)
Cloud computing is the architecture in which cloudlets are executed by the virtual machines. The most applicable virtual machines are selected on the basis of execution time and failure rate. Due to virtual machine overloading, the execution time and energy consumption is increased at steady rate. In this paper, BFO technique is applied in which weight of each virtual machine is calculated and the virtual machine which has the maximum weight is selected on which cloudlet will be migrated. The performance of proposed algorithm is tested by implementing it in CloudSim and analyzing it in terms of execution time, energy consumption.